Precipitation behavior of BN in low carbon boron-bearing steel - SHI Cheng-bin; LI Jing; YU Lu; QI Yong-feng; LIU Wei-jian; ZHANG Zhi-ming (工程科学学报)
The low carbon boron-bearing steel with 0.0045% boron and 0.0039% nitrogen was investigated, the thermodynamics and kinetics of precipitation and growth of BN during liquid steel solidification were studied. The effect of cooling conditions on the precipitation and growth of BN was experimentally investigated. The results show that BN can only precipitate at the solidifying front where the solid fraction is greater than the calculated critical value of 0.981 due to the segregation of boron and nitrogen. There is a serious segregation of boron and nitrogen with the increase of the solid fraction at the solidifying front. The diffusion of nitrogen in liquid steel is the rate-controlling step of BN growth because the boron content in the remaining liquid steel is much higher than that of nitro-gen when the solid fraction is close to 1. The change in cooling rate of liquid steel has negligible effect on the segregation of boron and nitrogen. However, the size of BN precipitates decreases greatly with increasing the cooling rate.